2017
DOI: 10.1016/j.fuel.2017.02.075
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nozzle geometry over ignition delay and flame lift-off of reacting direct-injection sprays for three different fuels

Abstract: h i g h l i g h t sSimultaneous Schlieren and OH * chemiluminescence visualizations are carried out with different techniques. The effect of nozzle geometry is analyzed for three different fuels along a wide test matrix in reactive conditions. Analysis of spray tip penetration, lift-off length and ignition delay. A total of 162 different test conditions are evaluated in the high temperature/high pressure test rig. The experimental database will be published and available for model validation. a b s t r a c tTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 53 publications
(146 reference statements)
0
18
0
1
Order By: Relevance
“…According to Fig. (1), the chosen Slot cross section is formally related to the circular one by the following equations (1)(2)(3)(4), which are directly derived from the adopted section geometries. Table 1 After drilling, the two nozzles have been hydro-ground.…”
Section: Flatmentioning
confidence: 99%
“…According to Fig. (1), the chosen Slot cross section is formally related to the circular one by the following equations (1)(2)(3)(4), which are directly derived from the adopted section geometries. Table 1 After drilling, the two nozzles have been hydro-ground.…”
Section: Flatmentioning
confidence: 99%
“…Liu et al [13], showed in their study how the low temperatures affect the combustion of the Diesel jet increasing the lift-off length and the delay time, together with low temperatures, the injection pressure has little significance over the length of the Lift-off and delay time. As the temperature affects the lift-off length, the geometry of the nozzle is another important parameter to be considered as demonstrated by Payri et al [14], which considered three fuels and two nozzles with different geometries; one consisted of a conical shape, while the other had a circular hole, but with a diameter 8.6% larger than the conical one. The results obtained experimentally indicated that the conical geometry has a longer lift-off length when compared to circular geometry, and a shorter delay time, highlighting that it may be due to the liquid length evaporating faster than in the circular nozzle.…”
Section: 2theoretical-experimental Study Of Injectionmentioning
confidence: 99%
“…Researchers have used Schlieren imaging to analyze the transient vapor phase of the diesel sprays in both nonreactive and reactive conditions. With this technique it is possible to measure simple macroscopic parameters, like spray tip penetration and spreading angle [2,3], to more complex variables, like ignition delay [4][5][6][7] or even lift-off length [8]. It is not only fundamental knowledge to understand how boundary conditions affect these variables, but the experimental data is necessary to validate computational tools, such as 1-D models or computational fluid dynamics (CFD).…”
Section: Introductionmentioning
confidence: 99%
“…It is not only fundamental knowledge to understand how boundary conditions affect these variables, but the experimental data is necessary to validate computational tools, such as 1-D models or computational fluid dynamics (CFD). The two most common Schlieren configurations are single-pass (SP) [2,[5][6][7][8][9] and double-pass (DP) [3,[10][11][12][13]. Typically, the first setup is used for axially drilled single-orifice nozzles, where vessels with multiple optical accesses allow line of sight visualization.…”
Section: Introductionmentioning
confidence: 99%